Evaluation of Chelating Agents with Different Biodegradability Rates on the Enhanced Phytoremediation Efficiency of Ornamental Species (Amaranthus caudatus and Tagetes patula) in Cadmium Contaminated Soils - Nastaran Aghelan; Soheil Sobhanardakani; Mehrdad Cheraghi; Bahareh Lorestani; Hajar Merrikhpour (Muhandisī-i Bihdāsht-i Muḥīṭ, 2020)
Background & Objective: Nowadays, since increasing environmental pollution particularly soil contamination can cause adverse health effects, kind of methods such as phytoremediation techniques are commonly used to remediate organic, inorganic and nuclear pollutants from contaminated sites. Therefore, this study was conducted to assess of chelating agents with different biodegradability rates on the enhanced phytoremediation efficiency of Amaranthus caudatus and Tagetes patula as ornamental species in cadmium contaminated soils in 2018. Materials & Methods: In pot experiments, the soil specimens were moderately artificially contaminated by cadmium chloride (50 and 100 mg/kg).            Then 2.5 mmol/kg of EDTA, 2.0 mmol/kg of salicylic acid (SA) and 2.5 mmol/kg of citric acid (CA) solution were added to the contaminated soils to study the influence of these chelating agents on phytoremediation efficiency by studied ornamental plants. Finally, after acid digestion of cultivated soil, roots and stems of A. caudatus and T. patula, the Cd content was determined using ICP-OES. Results: The results showed that after 60 days of pots irrigation, the maximum mean content of Cd (mg/kg) in cultivated soil, root and stem samples of A. caudatus with 1.87, 4.50 and 1.89 were found in the SA, EDTA and SA treatments, respectively. Moreover, the maximum mean content of Cd in cultivated soil, root and stem samples of T. patula with 1.86, 1.18 and 3.10 were found in the control, CA and SA treatments, respectively. Also, the values of translocation and bioconcentration factors indicate that A. patula can be considered to be potential plant species for phytostabilization and phytoextraction of cadmium, respectively. Conclusion: The results reported in this study show that the organic acids such as SA and CA have considerable role in soil refining electrokinetic or enhance of soil electrokinetic bioremediation through mechanisms resembling hormonelike effects, phosphate  release and dissolution, enhancing of cadmium mobility and some enzymatic activities, microstructural variations and retention capacity decreasing of clay particles. Therefore, due to the desirable effects of organic acids as chelate agents to enhancing phytoremediation efficiency of hyperaccumulator species use of these compounds in the cleanup of contaminated soil is recommended.